Accuracy of Physician Reporting in Routine Public Health Surveillance for Hepatitis C Virus Infection. (January 2014) - Jochem, Klaus; Leclerc, Pascale; Maurais, Emilie; Tremblay, Claude; Cox, Joseph
Objective: From January 2007 to December 2008, the Montréal Public Health Department sent postal questionnaires to physicians and conducted patient interviews for all those newly diagnosed with hepatitis C virus (HCV) infection. We evaluated physician responses to risk factor questions for non-acute HCV cases. Methods: We compared physician and patient responses with each of nine risk factor questions, determined the sensitivity and specificity of physician responses compared with patient responses, and evaluated agreement using Gwet's agreement coefficient (AC1 ). We ranked risk factors and compared the distributions by principal exposure category according to physician reporting vs. patient interview using the Chi-square test. Results: The completeness of physicians' responses (yes, no, or unknown) varied by risk factor question from 90.8% to 96.7%. For risk factors present among more than 5% of cases, sensitivity of physician responses ranged from 26.9% to 87.7% and specificity ranged from 93.0% to 98.6%. The AC1 coefficients for agreement between physician and patient responses to lifetime risk factors considered most important in HCV acquisition were 0.80 for injection drug use, 0.95 for blood transfusion before 1990, and 0.86 for birth in a country with high HCV prevalence. Risk distributions by principal exposure category according to physician reporting vs. patient interview were not statistically different (χ 2 [4] = 2.17, p =0.704). Conclusion: Postal questionnaires completed by physicians appear valid for determining the principal exposure category among non-acute HCV cases. Physician reporting can be a useful and low-cost component of routine HCV surveillance.